2002
DOI: 10.1080/02652040110081352
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide-loaded nanospheres: analysis of the matrix structure by thermal and spectroscopic methods

Abstract: This study reports on the preparation and evaluation of cyclophosphamide loaded-polyalkylcyanoacrylate nanospheres obtained by emulsion polymerization. Characterization by differential scanning calorimetry, infrared spectroscopy and X-ray diffraction can reveal state dispersion of the drug inside the nanospheres. Such information predicts the stability of the particles and the drug release behaviour. The study has indicated the prescence of a molecular dispersed system. The drug release behaviour was also stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Butylcyanoacrylate spheres containing cyclophosphamide have been used to treat ocular inflammation in the inner cavity of the eye. 9,10 It demonstrated that cyclophosphamide was incorporated in butylcyanoacrylate spheres for ocular drug delivery, showing the treatment of severe ocular inflammation without any corneal irritation. Rat gliomas have also been treated using cyclophosphamide-loaded biodegradable polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butylcyanoacrylate spheres containing cyclophosphamide have been used to treat ocular inflammation in the inner cavity of the eye. 9,10 It demonstrated that cyclophosphamide was incorporated in butylcyanoacrylate spheres for ocular drug delivery, showing the treatment of severe ocular inflammation without any corneal irritation. Rat gliomas have also been treated using cyclophosphamide-loaded biodegradable polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…40 The electrosprayed gliadin nanoparticles enabled the physical entrapment of the drug, showing that cyclophosphamide could disperse in the polymeric matrix of nanoparticles, as previously described. 10 The lipophilic amino acid, one of the components in gliadin protein, bound to cyclophosphamide due to hydrophilic interactions. As a result, the gliadin-based nanoparticles could bind to a cyclophosphamide anticancer drug, as previously described.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Biodegradable polymer nanoparticles, typically consisting of polylactic acid (PLA), polyglycolic acid (PGA), or a copolymer of PLA and PGA, are being investigated for the delivery of proteins and genes [64,65], vaccines [66,67], anticancer drugs [68][69][70], ocular drugs [71,72], and cytokines [73]. Other polymers being investigated for nanoscale drug carriers include polyalkylcyanoacrylate [74], poly(3-hydroxybutanoic acid) (PHB) [75], poly(organophosphazene) [76], poly(ethylene glycol) (PEG) [77][78][79][80], poly(caprolactone) (PCL) [81,82], poly(ethylene oxide) (PEO) [83], and copolymers such as PLA-PEG [84,85]. Synthetic polymers, such as PEG, can be used to encapsulate biologic materials to create a more stable drug carrier.…”
Section: Polymer Structuresmentioning
confidence: 99%
“…Cyclophosphamide-loaded polybutylcyanoacrylate nanospheres were investigated to obtain a suitable and tolerated ocular delivery device for therapeutic applications involving treatment of severe ocular inflammatory processes that localize in the anterior chamber of the eye. 107,108 Local delivery of 4-hydroperoxycyclophosphamide (4HC derived from cyclophosphamide), was achieved via a controlledrelease biodegradable polymer to determine whether the use of a polymer vector can enhance efficacy. Ninety Fischer 344 rats implanted with 9L or F98 gliomas were treated with an intracranial polymer implant containing 0% to 50% loaded 4HC in the polymer.…”
Section: Alkylating Agentsmentioning
confidence: 99%